PENGARUH IMPLEMENTASI KURIKULUM MERDEKA, SARANA PRASARANA DAN KOMPETENSI GURU TERHADAP PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH ATAS DI KABUPATEN PIDIE - Turmizi Turmizi; Marwan Marwan; Munawar Munawar (Universitas Islam Negeri Sumatera Utara Medan, 2026)
Improving the quality of education is influenced by various factors, including curriculum policy, the availability of facilities and infrastructure, and teacher competence as the main implementers of learning. The Merdeka Curriculum policy is expected to enhance education quality through student-centered learning, competency strengthening, and the development of the Pancasila Student Profile. However, the success of its implementation greatly depends on school readiness, facility support, and teacher competence. Therefore, this study aims to analyse the effect of the implementation of the Merdeka Curriculum, facilities and infrastructure, and teacher competence on improving the quality of education in senior high schools in Pidie Regency.This study employs a descriptive quantitative approach with a population of 514 senior high school teachers in Pidie Regency and a sample of 225 teachers from 12 schools. Data were collected using a closed-ended questionnaire with a Likert scale ranging from 1 to 5 to measure the variables of Merdeka Curriculum implementation, facilities and infrastructure, teacher competence, and education quality. Validity and reliability tests were conducted to ensure the instrument’s reliability, while data analysis used descriptive and inferential statistics with the assistance of IBM SPSS version 26. The results show that the implementation of the Merdeka Curriculum has a positive and significant effect on education quality. Student-centered learning, varied learning methods, and character strengthening through projects have been proven to improve the quality of learning processes and outcomes. Facilities and infrastructure also have a significant effect on education quality, as the availability of adequate learning facilities creates a conducive learning environment. In addition, teacher competence has the most dominant influence on education quality, reaffirming the importance of pedagogical, professional, social, and personal competencies in supporting successful learning